2022
DOI: 10.1002/jsfa.11963
|View full text |Cite
|
Sign up to set email alerts
|

Reducing chilling injury in 'Palmer' mangoes submitted to quarantine cold treatment

Abstract: BACKGROUND Treatment with low temperatures can be used to quarantine mangoes against fruit‐fly infestation. However, mangoes can develop chilling injury (CI) when stored at temperatures below 13 °C. We demonstrated that the immersion in polyol solutions can alleviate CI symptoms in ‘Palmer’ mangoes stored at 8 °C. These suggest that polyols can be used to reduce CI in mangoes during quarantine at low temperatures. Thus, we investigated the efficacy of applying 0.1% (v/v) glycerol, propylene glycol, or sorbitol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 39 publications
(69 reference statements)
0
5
0
Order By: Relevance
“…The dissociation of the enzymatic defence system (DHAR, GR, and ATPase) in tissue and with CI suggested that this was the primary mechanism of CI reduction in mangoes regardless of treatment. Although studies have linked DHAR, GR, and ATPase activities to decreased oxidative damage produced by CI in mangoes [ 64 ], the non-enzymatic defence mechanism (AsA and TFC) should also be evaluated, since the mango showed no oxidative damage over the storage period [ 59 , 60 , 65 ]. TEAC is an antioxidant capacity measure that quantifies a substance’s ability to neutralise free radicals, which are chemicals that can cause cell damage and contribute to the development of many disorders.…”
Section: Discussionmentioning
confidence: 99%
“…The dissociation of the enzymatic defence system (DHAR, GR, and ATPase) in tissue and with CI suggested that this was the primary mechanism of CI reduction in mangoes regardless of treatment. Although studies have linked DHAR, GR, and ATPase activities to decreased oxidative damage produced by CI in mangoes [ 64 ], the non-enzymatic defence mechanism (AsA and TFC) should also be evaluated, since the mango showed no oxidative damage over the storage period [ 59 , 60 , 65 ]. TEAC is an antioxidant capacity measure that quantifies a substance’s ability to neutralise free radicals, which are chemicals that can cause cell damage and contribute to the development of many disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Under standard cold quarantine treatment conditions (1 • C for 14 days), immersion in a solution containing 0.1% sorbitol was the most effective in mitigating Cis. This effect was associated with lower MDA and H 2 O 2 concentrations and PPO activity levels, as well as higher SOD, CAT, and APX enzyme activity and ascorbic acid levels, especially in the pericarp [28]. The combination of immersion of 'Palmer' mangoes in solutions containing 2.5% sorbitol with controlled atmosphere (CA) storage reduced CIs through the activation of non-enzymatic (ascorbic acid and total phenolic compounds) and enzymatic (SOD, CAT, and APX) mechanisms in fruits kept at 8 • C for 30 days [28].…”
Section: Introductionmentioning
confidence: 91%
“…This effect was associated with lower MDA and H 2 O 2 concentrations and PPO activity levels, as well as higher SOD, CAT, and APX enzyme activity and ascorbic acid levels, especially in the pericarp [28]. The combination of immersion of 'Palmer' mangoes in solutions containing 2.5% sorbitol with controlled atmosphere (CA) storage reduced CIs through the activation of non-enzymatic (ascorbic acid and total phenolic compounds) and enzymatic (SOD, CAT, and APX) mechanisms in fruits kept at 8 • C for 30 days [28]. Despite these results, there is no information available regarding the effectiveness of sorbitol treatment in other storage atmospheres and/or in combination with lower temperatures.…”
Section: Introductionmentioning
confidence: 91%
“…As a typical tropical plant, mango is sensitive to cold temperature [ 26 ], especially frequent extreme cold weather, which has significantly threatened to mango production in recent years [ 27 ]. However, few studies have revealed the molecular basis of cold stress response in mango trees, even if the cold storage of detached fruits has been well studied [ 28 ]. Considering that overexpression of CNGC genes promotes rice cold tolerance, we conducted genome-wide analysis of the CNGC family in mango and evaluated its expression in mango tissues, as well as that under cold stress [ 29 ].…”
Section: Introductionmentioning
confidence: 99%